Gender Symbolic Interactionism Efforts to Create Ukhuwah (Study on PMI Volunteer Corps, Pekalongan Regency) - Suwandi Aris Wibowo; Muqoyimah Muqoyimah (LPPM IAIN Parepare, 2022)
The object of the research is the volunteers of KSR PMI Pekalongan Regency. Researchers found the carrion between of gender communication and the interaction of symbols between volunteers in pro-social practices in the humanitarian field. The author conducted research within the KSR PMI organization in Pekalongan to know how the symbolic interaction of its gender in realizing ukhuwah together research each er used phenomenological qualitative meta od with purposive sampling technique. The results showed that the symbolic interaction between KSR volunteers was work efficiency, where there were no gaps in the task process of PMI KSR volunteers. The division of labor over the gender of the volunteers of KSR PMI Pekalongan Regency has differences between male and female volunteers. But even the difference is based on the principle of specialization and individual volunteer abilities. This research can build a correct and gender-biased view of the body of the PMI KSR and prioritize the main goals and tasks in the community. The research has limitations in the symbolic interactions occur in the PMI KSR. The author only study in the narrative qualitative paradigm and only produces signs as symbol.